Gaining a mobile sense of place with collector for ArcGIS. Issue 4 (2nd October 2018) - Pánek, Jiří; Glass, Michael
ABSTRACT: Mobile technology is increasingly widespread in geographic instruction, raising questions about how to integrate and analyse data from multiple users. Collector for ArcGIS allows researchers to gather multi-sensory field data, and is therefore a prospective way to integrate qualitative and quantitative information. We evaluate students' experience using Collector in an exercise that considered the senses of place in a research neighbourhood. Collector proved somewhat effective, yet requires significant technical expertise to integrate into research assignments. We describe the strengths and weaknesses of mobile applications such as Collector, and provide solutions for faculty interested in mobile applications for the field-based capture of multi-sensory data.